Solid-Oxide Fuel Cells in Power Generation Applications: A Review - M. Budzianowski, Wojciech; Milewski, Jaroslaw (Recent Patents on Engineering, 2011)
Fuel cells enable to convert the chemical energy of fuels directly into electricity, i.e. without involving any thermo-mechanical energy conversion steps. Thus fuel cells are not limited by the Carnot efficiency experienced by conventional thermo-mechanical power generators. From variety of available fuel cells, solid-oxide fuel cells (SOFCs) seems to be well-suited for large-scale power generation applications. However, for large-scale deployment of SOFCs further technological advancements are still needed. Therefore, the current review investigates significant patented developments utilising SOFCs in power generation applications over the last 5 years (2007-2011). The focus is on key technical barriers limiting the development of SOFC technology in relation to power generation applications. The review presents and discusses appropriate solutions disclosed in recent patents. The key technical barriers together with their patented solutions relate to the thermal resistance of SOFC's materials, fuel reforming techniques, energy conversion efficiency, the use of novel materials, architecture design, and techniques for improved fuel utilisation.
Keywords: combustion